Evaluation of the Effects of Schisandra chinensis on the Myocardium of Rats with Hyperthyroid Heart Disease by Using Velocity Vector Imaging Combined with the Estimation of p53 Expression and Calmodulin Activity. (30th July 2020) - Hou, Rui; Jin, Xuanshun; Gao, Yihua; Sun, Dandan; Ma, Weiping; Sun, Puyin; Jin, Chengzi
Abstract : Schisandra chinensis (SC) is reported to improve myocardial ischemia. Velocity vector imaging (VVI) is a noninvasive technique for evaluating myocardial function in humans, while few reported on the application in animals. In this study, we aimed to evaluate the improved effects of SC on the myocardium of Sprague Dawley rats having hyperthyroid heart disease (HHD) using VVI technique. HHD models were established by injecting daily with subcutaneous levothyroxine (0.5 mg/kg). Then, the SC group was administered the aqueous extract of SC (2 g/kg) once daily, while the HHD and control (CON) groups were administered the same amount of distilled water daily. All the rats were provided the same amount of food and water daily, and the intervention was stopped after 28 days. The efficacy of SC in HHD rats was evaluated by ultrasound VVI. The serum total triiodothyronine level, total thyroxine level, N-terminal pro-brain natriuretic peptide expression, p53 expression, and calmodulin (CaM) activity were assessed by western blotting, Hematoxylin-Eosin and Masson staining, and electron microscopy. The results indicated that SC significantly improved the systolic velocity, diastolic velocity, strain, systolic strain rate, and diastolic strain rate of the heart by significantly reducing p53 expression and CaM activity (P < 0.05 ), improving myocardial fibrosis in HHD rats. Also, VVI can be a valuable tool for the evaluation of myocardial function in HHD rats.